الإشراف الحكومي على الصناعات بالقاهرة في فترة القرنین 10-11هـ. / 16-17م. - عبدالغني، فاطمة الزهراء محمد علي (جامعة عين شمس - مركز الدراسات البردية والنقوش, 2017)
يتناول بحث الدراسة موضوع الإشراف الحكومي على الصناعات بالقاهرة في فترة القرنين 10/ 11 هـ- 16/ 17 م، من حيث إجازة العمل، متابعة ضوابط العمل في الصنعة، الاختصاصات في تصنيع المنتج، الشهادة على تعليم الصنعة وإثباتها في المحكمة، الإنفاق على تصنيع المادة الخام، ضوابط تسويق المنتج المصنع، تنظيم الأنشطة المشتركة بين الحرف الصناعية، تنظيم الشركات بين الحرفين، توزيع الحرفيين على الإطار الجغرافـي للمدينة، ويتناول البحث أيضا مهام وتعيين وعزل شيخ الطايفة، وكذلك سلطة المحتسب في تنظيم أمور الصناعة.
The search is a study of the government supervision of the industries in Ottoman Cairo in the period 10-11 /16-17. The craft communities represented the authorities in a framework that enables them to control various aspects of the society, this is exactly what we find in the authority of the Shaykh al-Ta'ifah on their sects, and thus represented an administrative link between Authority and people. In general, the industrial crafts had specialized markets where the manufactured product was sold, such as the markets of goldsmiths, blacksmiths, etc. The craftsman worked in the purchase of raw material, then manufactured and then promoted, thus maintaining the craft on its technical level in producing the goods, Local and international, where export to abroad and found a place among other products and is supervised by the government on the quality of manufactured goods and exported abroad. The supervision of the role of sheikhal-Ta'ifah in the work permit and the joining of industry to the community, and oversee the controls of the work within the table, and oversee the geographical distribution of the communities in Cairo, and determine the terms of reference of each industrial community in common The follow-up of the marketing of the product manufactured in the markets, the emergence of the authority of the beneficiary in settling disputes between the sects, the authority to distribute the manufactured product, and the restrictions on joining the community. The emergence of the role of the accountant in the absence and weakness of the authority of Sheikh al-Ta'ifah, and the absence of the role of accountant in the supervision of industries.
Keywords: الإشراف الحكومی -- المنشآت الصناعية -- الحرف الصناعية -- العصر العثمانى -- مدينة القاهرة -- مصر